2021
DOI: 10.1002/pssr.202100242
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer‐Thick GaN/AlN Multilayer Heterostructures for Deep‐Ultraviolet Optoelectronics

Abstract: Recent progress in the development of monolayer (ML)‐thick GaN/AlN multilayer heterostructures for deep‐ultraviolet (UV) optoelectronics is reviewed. Analysis of both plasma‐assisted molecular beam epitaxy and metal–organic vapor phase epitaxy shows that extreme interface sharpness and sub‐ML accuracy in setting the layer thickness are attractive features of the former, whereas the lowest density of threading dislocations and wide possibilities for the implementation of various 2D growth mechanisms are the adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 136 publications
1
21
0
Order By: Relevance
“…An internal quantum efficiency of up to 50% was also demonstrated by Kawakami's group for ML-thick GaN/AlN MQW structures emitting below 250 nm, which were grown using MOVPE [32]. We have recently published a review on such ML-thick GaN/AlN heterostructures [33].…”
Section: Introductionmentioning
confidence: 71%
“…An internal quantum efficiency of up to 50% was also demonstrated by Kawakami's group for ML-thick GaN/AlN MQW structures emitting below 250 nm, which were grown using MOVPE [32]. We have recently published a review on such ML-thick GaN/AlN heterostructures [33].…”
Section: Introductionmentioning
confidence: 71%
“…A pulsed (continuous wave) output power of 160(39) mW was at 240 nm obtained with a standard e‐beam gun, while the pulsed output power increased up to 1 W with a high‐current e‐gun. [ 33 ] These results indicate a high efficiency of radiative recombination in such ultrathin (ML‐thick) QWs. The initial study of these heterostructures using a TEM revealed periodic ML‐range compositional inhomogeneities (ordering) in the AlGaN barrier layers, the origin of which and the influence on the optical properties of the structures were not completely clear at that time.…”
Section: Introductionmentioning
confidence: 91%
“…Since 2008, our group has been studying the PA MBE growth of layers and heterostructures in the (Al,Ga)N material system. [ 31–33 ] A unique feature of this technology is the possibility of the low‐temperature ( T S ≤ 700 °C) growth of AlGaN‐based heterostructures under metal‐enriched conditions, which ensure atomically sharp interfaces in the ML range (the thickness of 1 ML is ≈0.25 nm). The suppression of Ga segregation and intermixing in the AlGaN‐based heterostructures at low growth temperatures, as well as the possibility of the extremely fast (<0.5 s) control of growth molecular fluxes using electromechanical shutters of effusion cells, made it possible to develop a new method of sub‐ML digital alloying (SDA) to form Al x Ga 1− x N/Al y Ga 1− y N QWs as nominal {GaN/Al y Ga 1− y N} n ( y = 0−1, n = 1−10) SLs with GaN inserts having nominal thickness varying from a few MLs down to less than 1 ML.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrawide bandgap semiconductors, including AlN and high Al content AlGaN alloys, are considered technologically important for various applications including short wavelength ultraviolet (UV) light emitting, high-electron mobility transistors (HEMTs), and field emission, owing to their ultrawide and direct bandgap energies, large breakdown fields, and chemical stability. Moreover, they are widely used as buffer layers for III-nitride electronic and photonic devices. However, the lack of native substrate has posed a significant challenge for the development of AlN and high Al content AlGaN based device technologies. The large lattice mismatches with commonly available foreign substrates lead to many issues in the epilayers, such as large dislocation densities and cracks.…”
mentioning
confidence: 99%